2021
DOI: 10.1016/j.bcmd.2020.102525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, comorbidity and remission status on outcome of COVID-19 in patients with hematological malignancies

Abstract: Background There is scarcity of data on outcome of COVID-19 in patients with hematological malignancies. Primary objective of study was to analyse the 14-day and 28-day mortality. Secondary objectives were to correlate age, comorbidities and remission status with outcome. Methods Retrospective multicentre observational study conducted in 11 centres across India. Total 130 patients with hematological malignancies and COVID-19 were enrolled. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 25 publications
7
43
2
1
Order By: Relevance
“…This could be one of the reasons for high mortality in our study. Adverse effect of age and comorbidity in patients with haematological malignancy was previously demonstrated by our group [21].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This could be one of the reasons for high mortality in our study. Adverse effect of age and comorbidity in patients with haematological malignancy was previously demonstrated by our group [21].…”
Section: Discussionsupporting
confidence: 58%
“…This study revealed an increased risk of need for ICU admission, mechanical ventilation and death compared with Covid-19 patients without cancer [20]. We have earlier documented a high 60% mortality rate in patients with hematological malignancies with severe Covid-19 [21]. Mortality in present study with use of CPT is 45.5%.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…All patients with diabetes mellitus, chronic kidney disease and hyperthyroidism died (Fig. 3), probably due to, the instability in the general state of health that was confirmed by COVID-19 [15,13].…”
Section: Resultsmentioning
confidence: 92%